Impact of extraction mode on phytoconstituents and antidiabetic activity of extracts of Calotropis procera (Aiton) Dryand. - Sadaf Iftikhar; Khalid Hussain; Muhammad Saleem; Naureen Shehzadi; Farhat Saghir; Ayisha Shaukat; Surriya Naheed; Sidra Siddique (GarVal Editorial Ltda., 2022)
Context: The extraction mode plays a key role in extracting a particular type of pharmacologically active compounds that can be isolated as leads to develop novel therapeutic molecules. Aims: To evaluate the impact of extraction mode on extract yield, phytochemicals constituents, and antidiabetic activity of different parts of the Calotropis procera. Methods: The different parts extracts were prepared by maceration and Soxhlet extraction. The resulting extracts were subjected to determining phytochemical constituents and antidiabetic activity using in vitro models (inhibition of alpha-amylase, glucose uptake by yeast cell, and inhibition of non-enzymatic Hb-glycation). Result: The yield of extracts was higher in Soxhlet extraction in both solvents compared to maceration. Likewise, methanol extract of all the parts prepared by Soxhlet extraction exhibited higher contents of total polyphenols and tannins (430.2 ± 0.99 and 228.3 ± 3.8, respectively). On the other hand, total flavonoids and terpenoids were more in all parts prepared by maceration. The extract of flower and stem prepared by maceration exhibited 64.87 ± 0.720%, 70.32 ± 0.75%, and 56.86 ± 0.13% antidiabetic activity in alpha-amylase enzyme, non - enzymatic Hb glycation inhibition, and glucose enhancement in yeast, respectively (p<0.05) as compared to standards. The IC50 of alpha-amylase inhibitory assay and non-enzymatic Hb-glycation was 600 µg/mL and 420 µg/mL, respectively, and EC50 for glucose uptake assay was 400 µg/mL. Conclusions: This study revealed that maceration extracts with higher flavonoid and terpenoid content have higher antidiabetic action than Soxhlet extracts. This study will assist in the future for the isolation of antidiabetic compounds from the plant.